COMPARISON BETWEEN NUTRITIONAL STATUS AND VALUES OF THE PEDIATRIC SYMPTOM CHECKLIST 17 QUESTIONNAIRE CROSS-SECTIONAL STUDY AT 5 ELEMENTARY SCHOOLS IN CIHERANG VILLAGE - Santoso, Alexander Halim; Firmansyah, Yohanes; Dewi, Fransisca Iriani R; Agustina, Agustina; Satyanegara, William Gilbert; Edbert, Bruce; Warsito, Jonathan Hadi; Suros, Angel Sharon (HEARTY, 2024)
Child malnutrition, both over and undernutrition, is a serious problem affecting millions of children worldwide, with significant short- and long-term impacts on children’s health and development. This research study the correlation between dietary status and emotional and behavioural problem among primary school children in Ciherang Village. This study is a cross-sectional design in which children who satisfy the specified criteria will undergo weight and height measurements. Their body mass index (BMI) will be calculated and compared to the BMI-for-age chart (BMI/Age). Additionally, the children will complete the Pediatric Symptom Checklist 17 (PSC-17) questionnaire. A total of 246 children from 5 schools in the Ciherang area met the inclusion criteria. The analysis revealed a significant correlation between the average difference in body mass index and the total PSC 17 score (p-value=0.026). This study identified a comparison between children’s dietary health and emotional and behavioural disorders. This serves as a reminder of the significance of monitoring children’s development and implementing a well-rounded diet to promote children’s mental well-being.